Economic environment in fostering the internationalization of higher education institutions: what matters? - Mustakim, Siti Salina; Hassan, Aminuddin; Chen, Xiaofei (Human Resource Management Academic Research Society, 2024)
The article explores into a thorough examination of the profound influence of the economic environment on the internationalization of higher education in Guizhou province, China. Through a detailed analysis of various factors, a significant correlation between the economic landscape and efforts to internationalize higher education institutions in this Chinese province is acknowledged. The government's apparent oversight in managing funds dedicated to promoting internationalization and enhancing institutional infrastructure, shedding light on the challenges arising from this neglect is also discussed. Language barriers and cultural disparities emerge as critical considerations in the article. Beyond financial aspects, the complexities introduced by linguistic and cultural differences are underlined, indicating potential obstacles to the successful internationalization of higher education in Guizhou. The needs for more intensive government efforts to allocate and manage funds effectively is also discovered. Without strategic planning in this regard, the full potential of internationalization in higher education in Guizhou may remain unrealized. Cultural competency programs are also crucial to overcoming disparities and creating a globally aware learning environment. This article contributes to offer a nuanced understanding of the current scenario by highlighting the impact of the economic environment, funding mismanagement, language barriers, and cultural disparities, calling for strategic interventions and policy changes.